2014
DOI: 10.3109/00498254.2013.874610
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of chlorogenic acid and corydaline in DA-9701, a new botanical gastroprokinetic agent, in rats

Abstract: 1.Few studies describing the pharmacokinetic properties of chlorogenic acid (CA) and corydaline (CRD) which are marker compounds of a new prokinetic botanical agent, DA-9701, have been reported. The aim of the present study is to evaluate the pharmacokinetic properties CA and CRD following intravenous and oral administration of pure CA (1-8 mg/kg) or CRD (1.1-4.5 mg/kg) and their equivalent dose of DA-9701 to rats. 2.  Dose-proportional AUC and dose-independent clearance (10.3-12.1 ml/min/kg) of CA were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Rat plasma calibration standards were prepared at eight concentration levels by adding 2 μL working standard solution to 50 μL of drug-free rat plasma: 0.5, 1.0, 2.0, 5.0, 10.0, 25.0, 50,0, 100, and 200 ng/mL for CGA and NCGA, 2.5, 5.0, 10.0, 25.0, 50,0, 250, 500, and 1000 ng/mL for CCGA, CA, CA-3-G, and CA-4-G, and 12.5, 25.0, 50.0, 125, 250, 1250, 3750, and 5000 ng/mL for FA, respectively. 5 μL of 5% formic acid was added and vortex-mixed to improve the plasma stability of CGA, CCGA, and NCGA [ 24 , 32 ]. Quality control (QC) samples were prepared at the concentrations of 1.5, 25, and 160 ng/mL for CGA and NCGA, 7.5, 125, and 800 ng/mL for CCGA, CA, CA-3-G, and CA-4-G, and 37.5, 625, and 4000 ng/mL for FA in drug-free rat plasma and then stored at −80 °C until analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Rat plasma calibration standards were prepared at eight concentration levels by adding 2 μL working standard solution to 50 μL of drug-free rat plasma: 0.5, 1.0, 2.0, 5.0, 10.0, 25.0, 50,0, 100, and 200 ng/mL for CGA and NCGA, 2.5, 5.0, 10.0, 25.0, 50,0, 250, 500, and 1000 ng/mL for CCGA, CA, CA-3-G, and CA-4-G, and 12.5, 25.0, 50.0, 125, 250, 1250, 3750, and 5000 ng/mL for FA, respectively. 5 μL of 5% formic acid was added and vortex-mixed to improve the plasma stability of CGA, CCGA, and NCGA [ 24 , 32 ]. Quality control (QC) samples were prepared at the concentrations of 1.5, 25, and 160 ng/mL for CGA and NCGA, 7.5, 125, and 800 ng/mL for CCGA, CA, CA-3-G, and CA-4-G, and 37.5, 625, and 4000 ng/mL for FA in drug-free rat plasma and then stored at −80 °C until analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The doses of DA-9701 (80-328 mg/kg) in this study were based on the maximum tolerated dose of DA-9701 and assay sensitivity. 6) Linear pharmacokinetics of THP were observed following oral administration of DA-9701 at doses of 80, 164, and 328 mg/kg (equivalent to 0.36, 0.74, and 1.5 mg/kg THP). We inferred linearity from the constant dose-normalized AUC 0-8 h and C max values for THP (Table 1) (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the pharmacokinetics of chlorogenic acid and corydaline after intravenous and oral administration of pure chlorogenic acid, corydaline, or DA-9701 to rats were reported by our laboratory. 6) Linear pharmacokinetics of chlorogenic acid were observed following intravenous (1-4 mg/kg) and oral (1-8 mg/kg) administration of chlorogenic acid or DA-9701. The extent of absolute oral bioavailability (F) of chlorogenic acid was extremely low, 0.478-0.899%, possibly because of incomplete absorption, decomposition in the gastrointestinal (GI) tract, and/or presystemic metabolism.…”
mentioning
confidence: 99%
“…[5][6][7][9][10][11][12][13][14][15]30 We have already proven that DA-9701 decreases visceral pain in rats by down-regulating the level of phosphorylated extracellular signal-regulated kinase in the dorsal root ganglion and spinal cord. 12 Kim et al 11 also observed that the drug increased the pain threshold in rats with colorectal distension-induced visceral hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] DA-9701 has agonistic activity on serotonergic receptors, and antagonistic activity on dopaminergic receptors; thus it is known to increase gastric emptying and accommodation, and to reduce visceral hypersensitivity. [8][9][10][11][12][13][14][15][16][17] Pain-induced neural reflexes and postoperative intestinal inflammation can induce POI. 1 Abdominal pain after surgery can lead to the release of endogenous neuromuscular inhibitors, such as corticotropin-releasing hormone, norepinephrine, and nitric oxide synthase.…”
Section: Introductionmentioning
confidence: 99%